Performance Improvement of Non-Governmental Organisations through Financial Management: A Case study of Young Men's Christian Association of Ghana - Arthur, Benedict; Appiah-Kubi, Richard (Journal of Accounting, Business and Finance Research, 2020)
Non-governmental organizations (NGOs) in Ghana have a history of being short-lived. However, Young Men's Christian Association (YMCA) Ghana, on the other hand has achieved notable success by impacting millions of lives over 50 years of working in Ghana. Apparently, this research investigates into the key financial management practices of NGOs in Ghana using the case of YMCA Ghana. The study revealed that, the quality of Financial Management staff and their responsibility are the most effective financial management indicator in YMCA Ghana amongst all the other well-functioning indicators. Nevertheless, it is evident in the study that the challenge YMCA Ghana faces in its financial management practice is irregular external audit review of financial and accounting data. Therefore, it is recommended that frequent subscription for external audit services should be established in NGOs and also, cost effective monitoring, evaluation, accountability and learning (MEAL) programme management framework should be adopted by NGOs in Ghana.